PELAKSANAAN KAMPANYE PADA MASA RESES OLEH LEGISLATIF AGAM - Serlina, Annisa; Cahyono, Eko; Kurniasih, Hendi; Nashrullah, Muhammad Pandu; Saputri, Tasya Indah; Gusman, Erry (PUAN INDONESIA, 2024)
Recess is a period when DPRD members conduct activities outside the session, especially in their constituencies, to accommodate the aspirations of the community. Recess is conducted in order to carry out legislative and supervisory duties. However, if it is used for campaigning, it violates election rules that can harm democracy and tarnish the image of legislative members. Without a clear regulation, the practice of campaigning during recess can be a challenge for election supervisory institutions such as Panwaslu. This research uses an empirical legal approach method and was conducted in Agam Regency, West Sumatra Province, by collecting primary data through interviews with Panwaslu and secondary data from literature and legal documents. The analysis was conducted qualitatively to understand the impact and implications of campaign practices during the recess period on democracy and the integrity of legislative institutions.